Exploring stereotypes - Hempkin, Kirsten (ELOPE (Ljubljana), 2008)
It is widely accepted that the use of humour and jokes in particular brings a number of benefits to the EFL teacher. Not only can jokes help to establish a relaxed learning atmosphere, they can also serve as a context in which to study particular aspects of grammar, vocabulary and culture. However, jokes based on national and regional stereotypes tend to be ignored by EFL teachers, as their potential to cause offense has seen them deemed unsuitable for classroom use. The purpose of this paper is to present a different perspective: it is precisely the rather risky nature of these jokes which makes them ideal for classroom use, particularly in lessons with the specific aim of raising students' cultural awareness through the exploration of stereotypes.
Keywords: angleščina kot tuj jezik; cultural awareness; EFL classroom; kulturna ozaveščenost; pouk angleščine; Scottish jokes; Slovene jokes; slovenske šale; stereotipi; stereotypes; škotske šale